Antibacterial Activity of Piper Nigrum Dried Fruit Extract - Hussen, E. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Crade extract of dried fruit piper nigrum was made by useing sexhdet for three hours.The dried material was extracted with 95% ethanol and water as solvent.            A test was made to the extract effect in certain concentration to 32 Gram of negative bacterial isolates , collected from patient admitted to Ibn-AL-balade hospital . Ethanolic extract showed antibacterial activity against bacterial isolates and water extract reveled effectivnes.Such isolates showed highly sensitive to Norfacin and Impinene and less sensitve to Amoxicillin .